The Best Partner for the Family Review of Takhrīj al-Ḥadīṡ “Khiyārukum Khiyārukum Linisāihim” in the Book of Sunan Al-Tirmiżī - Nur Mazaya Hurin In; Mohammad Ikhwanuddin; Salman Al Farisi; Thoat Stiawan; Gàndhung Fajar Panjalu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
In the Islamic context, the quality of the relationship between husband and wife is greatly influenced by the husband's character, which is measured based on the hadith